2022
DOI: 10.1021/acssuschemeng.1c06723
|View full text |Cite
|
Sign up to set email alerts
|

Protection Strategies for the Conversion of Biobased Furanics to Chemical Building Blocks

Abstract: In recent years, the urgency to replace fossil-based resources by renewable biomass for obtaining chemical building blocks has only increased. Carbohydrate-derived furanic compounds are regarded as promising platforms for a renewable value chain. The high reactivity of such biobased intermediates requires the development of novel catalytic chemistry to enhance product yield. The protection of reactive functional groups provides a way to improve the product selectivity. Such protection strategies are common pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…More detailed protection strategies were summarized in a very recent review. 27 Another issue for handling HMF arises from the negative effect of trace impurities on the catalytic conversions of HMF. 28 HMF synthesis typically uses unconventional solvents such as dimethyl sulfoxide (DMSO), and the presence of trace DMSO greatly affects the hydrogenation of HMF.…”
Section: Introductionmentioning
confidence: 99%
“…More detailed protection strategies were summarized in a very recent review. 27 Another issue for handling HMF arises from the negative effect of trace impurities on the catalytic conversions of HMF. 28 HMF synthesis typically uses unconventional solvents such as dimethyl sulfoxide (DMSO), and the presence of trace DMSO greatly affects the hydrogenation of HMF.…”
Section: Introductionmentioning
confidence: 99%
“…Although we did not consider the catalyst or molecular oxygen on the metal support in this study, the results shown in this paper suggest a deeper understanding of humin formation in various basic solutions and the effect of acetal protection on HMF. [36][37][38]…”
Section: Discussion On the Fdca Formation From Hmf And Pd-hmf Under B...mentioning
confidence: 99%
“…Protection of the highly reactive formyl group as its acetal with 1,3-propanediol (PD) suppresses such undesirable side reactions and allows the use of concentrated HMF solutions (10-20 wt %) for various hydrogenation and oxidation reactions. [28][29][30][31][32][33] We earlier established the potential of acetalized HMF with PD (PD-HMF) as a reactant in the one-pot oxidation and oxidative esterification with Au/CeO 2 and two equivalents of Na 2 CO 3 to synthesize FDCA (> 90 %) and MFDC (> 90 %), respectively, using concentrated PD-HMF solutions (> 10 wt %) (Schemes 1A and 1B). [30,31] The six-membered cyclic acetal ring in PD-HMF suppresses byproduct formation in concentrated solutions.…”
Section: Introductionmentioning
confidence: 99%